2005
DOI: 10.1504/ijram.2005.006705
|View full text |Cite
|
Sign up to set email alerts
|

Proposed fire safety strategy on airport terminals

Abstract: Fire safety strategy for airport terminals will be proposed in this paper. The local airport terminal is taken as an example. Special features of airport terminals will be outlined. The retail areas are identified as places with higher fire risk. Standards, codes and design guidelines used overseas are reviewed and compared with the local codes. Based on the study, fire safety strategy is suggested to have four parts:• passive building construction for fire safety• active fire protection systems or fire servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fire reports with multiple consequences also showed that in addition to minor and major damages and interruptions in activities, most fires will also have life-threatening consequences for residents, which emphasizes the importance of considering fire risk for activities and people. 14,15 The reasons for the high risk in these centers can be attributed to the lack of ventilation to clear the smoke, the lack of emergency exit routes and passageways suitable for the population of the centers, the lack of automatic or manual fire extinguishing equipments, the lack of water-based fire extinguishing systems and accessibility. Also, as the GIS map showed (Figure 4), the density of the centers in one street of the city and the low capacity of this street to move in times of emergency have made the risk of fire in some centers very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire reports with multiple consequences also showed that in addition to minor and major damages and interruptions in activities, most fires will also have life-threatening consequences for residents, which emphasizes the importance of considering fire risk for activities and people. 14,15 The reasons for the high risk in these centers can be attributed to the lack of ventilation to clear the smoke, the lack of emergency exit routes and passageways suitable for the population of the centers, the lack of automatic or manual fire extinguishing equipments, the lack of water-based fire extinguishing systems and accessibility. Also, as the GIS map showed (Figure 4), the density of the centers in one street of the city and the low capacity of this street to move in times of emergency have made the risk of fire in some centers very high.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fact that these centers are visited by people from all people with different ages and mobility limitations, it is very important to pay attention to fire conditions. Fire reports with multiple consequences also showed that in addition to minor and major damages and interruptions in activities, most fires will also have life‐threatening consequences for residents, which emphasizes the importance of considering fire risk for activities and people 14,15 …”
Section: Discussionmentioning
confidence: 99%